Analisis Kualitas Internet Marketing Berbasis Aplikasi Android â€œFeuniskamarketâ€ - Diana Ambarwati; Iing Sri Hardiningrum; Nur Hidayati (Fakultas Ekonomi Universitas Kadiri, 2018)
This study aims to analyze the quality of Internet Marketing based on the Android application